Enzymatic degradation of the hydrogels based on synthetic poly(α-amino acid)s - Sedlačík, Tomáš; Studenovská, Hana; Rypáček, František (Journal of materials science. Materials in medicine, 2011)
Biodegradable hydrogels are studied as potential scaffolds for soft tissue regeneration. In this work biodegradable hydrogels were prepared from synthetic poly(α-amino acid)s, poly(AA)s. The covalently crosslinked gels were formed by radical copolymerization of methacryloylated poly(AA)s, e.g. poly[N (5)-(2-hydroxy-ethyl)-L-glutamine-ran-L-alanine-ran-N (6)-methacryloyl-L-lysine], as a multifunctional macro-monomer with a low-molecular-weight methacrylic monofunctional monomer, e.g. 2-hydroxyethyl methacrylate (HEMA). Methacryloylated copolypeptides were synthesized by polymerization of N-carboxyanhydrides of respective amino acids and subsequent side-chain modification. Due to their polypeptide backbone, synthetic poly(AA)s are cleavable in biological environment by enzyme-catalyzed hydrolysis. The feasibility of enzymatic degradation of poly(AA)s alone and the hydrogels made from them was studied using elastase, a matrix proteinase involved in tissue healing processes, as a model enzyme. Specificity of elastase for cleavage of polypeptide chains behind the L-alanine residues was reflected in faster degradation of L-alanine-containing copolymers as well as of hydrogels composed of them.
Keywords: Methacrylates; Gels; biodegradace; Cartilage; biokompatibilní materiály; methakryláty; Pancreatic Elastase; Time Factors; časové faktory; Polymers; tkáňové inženýrství; Hydrogels; Cross-Linking Reagents; chemické modely; regenerace nervu; reagencia zkříženě vázaná; magnetická rezonanční spektroskopie; peptidy; Biocompatible Materials; Nerve Regeneration; gely; hydrogely; pankreatická elastasa; polymery; chrupavka; Biodegradation, Environmental; Models, Chemical; Tissue Engineering; Amino Acids; Magnetic Resonance Spectroscopy; aminokyseliny; Peptides